PEMANFAATAN MEDIA SOSIAL TERHADAP PARTISIPASI KEWARGAAN DIGITALGENERASI Z DI INDONESIA : LITERATURE REVIEW - Achmad Ramdani; Adi Satria Nugraha; Andrea Putri Kyrana; Haidar Alia Az Zahra; Muhammad Reynal Abipraya; Wadaa’ah Nabila (CV. Denasya Smart Publisher, 2026)
Social media has become a significant arena for Generation Z to interact, express opinions, and engage with public issues. The high intensity of digital platform usage highlights the need to understand how social media contributes to shaping digital civic participation among young people. This study aims to analyze the role of social media in developing Gen Z’s digital civic engagement through a qualitative literature review. The analysis draws on academic articles indexed in Sinta and other relevant publications from 2020–2025, interpreted using Choi’s (2016) Digital Citizenship Theory. The findings indicate that social media enhances access to information, supports involvement in digital campaigns and public discussions, and strengthens expressions of online citizenship. However, the quality of participation is influenced by users’ digital literacy and ethical awareness. The study concludes that social media has strong potential to foster digital citizenship among Gen Z, provided that digital competencies and ethical media practices are continuously improved. This study contributes academically by providing a systematic mapping of the role of social media in shaping Generation Z’s digital citizenship based on Choi’s theoretical framework, and by offering a conceptual foundation for the development of digital citizenship education policies and future research in the fields of communication and digital civic engagement.